Náboženství a emigrace 20. století: český případ = Religion and migration in the 20th century : the Czech case - Nešpor, Zdeněk R. (Religio, 2003)
Recent social science in many cases sees certain circumscriptions of modern, post-Enlightenment antireligious scientific approaches and goes backwards. As it can be seen in the case of the so-called new economic sociology, it deals with religious values and institutions, which provide an important symbolic frame of social behaviour. One good example is the topic of international migrations, which have been influenced by religious factors even in the 20th century. This article provides an analysis of Czech emigration to the West during the communist era and the return of these emigrants to the Czech Republic in the 1990s from such point of view. ...